Procesos productivos de la Arrocera El Rey S.A del cantón Daule, provincia del Guayas, periodo 2022. - Pibaque Méndez, Dayanara Belén (2023)
The study conducted in the production area aims to evaluate the production processes carried out in the rice mill, through the design of a new planning to improve production processes, and is closely related to the research line Financial, administrative, tax, audit and control management and is framed in the sub-line marketing and commercialization, the methodology used was integrated quality management system, which allowed us to propose changes for the improvement of production processes, the technique to be used are the interview and surveys, which allowed us to collect information and identify areas that need improvement, The results obtained in relation to the satisfaction of the quality of the type of rice produced by the employees reflect being moderately satisfied, this is due to the fact that when production is in progress, the employees mismanage the machinery, on the other hand, The company has not been able to improve the production processes, therefore, it has not been able to meet the objectives set, as one of the consequences the company is losing potential customers and has not been able to keep up with the competition.